Analisis Pengaruh Total Asset Turnover, Book To Market Ratio, Debt Equity Ratio Terhadap Expected Return Dengan Trading Volume Acitivity Sebagai Variabel Intervening (Studi Pada Perusahaan Perbankan yang Terdaftar pada BEI Periode 2010-2014) - Aprisilya, Tiari; Mawardi, Wisnu (Diponegoro Journal of Management, 2016)
The purpose of this study is to investigate: (1) The effect of total asset turnover (TATO), book to market ratio (BMR), and debt equity ratio (DER) to trading volume activity (TVA), (2) The effect of of total asset turnover (TATO), book to market ratio (BMR), debt equity ratio (DER), and trading volume activity (TVA) to the expected return (E(Ri)), (3) The effect of total asset turnover (TATO), book to market ratio (BMR), and debt equity ratio (DER) to the expected return (E(Ri)) through trading volume activity (TVA) as an intervening variable. Population of this research is 45 banking companies listed in Indonesia Stock Exchage. After used purposive sampling technique, then obtained total sample of 16 companies listed in Indonesia Stock Exchage 2011-2014. Path analysis used to be analysis technique using program SPSS 20 for windows to determine the effect of mediation. The result of this study showed that TATO and BMR significantly positiveÂ  effect on TVA. DER have positif effect on TVA but not significant. TATO, BMR, and DER have positif effect on E(Ri) but not significant. TVA significantly positive effect on E(Ri). The result of sobel test showed that TVA can used as intervening variable because significantly positive mediate the relation between TATO and BMR toward E(Ri).